Al-Muá¸Ärabah Min Wujhat Naáºr al-fiqh wa-Tajribat Bank al-SyarÄ«ah - Arief, Abd Salam (Al-Jamiah: Journal of Islamic Studies, 2004)
In Indonesian society, mudhÄrabah is one of sharÄ«ah economics systems that have been performed since long time ago in rural society. One example of mudhÄrabah is that landowners give the authority to other people to manage their lands and to share their crops. In fact, the prophet Muhammad has also done in his time of a such kind mudhÄrabah system in his society. In doing so, two parts are involved, the investor (shÄhih al mÄl) and the manager of the land (al-mudhÄrib). Nowadays, mudbÄrabah is an Islamic economics system that is offered by sharÄ«ah banks to attract more customers. In applying this system, mudhÄrabah can be seen in two ways, as a system and as a product. MudhÄrabah as a system is when it is used as guidance by a bank in its transactions. i,e., Partnerships agreement between the owner of the capital and the manager of a business is based on outcomes sharing. MudbÄrabah as a product was applied in two ways in sharÄ«ah banks, i.e. the bank as the owner of the capital and the bank as the manager of a business. This article illustrates the way that nudhÄrabah is applied in sharÄ«ah banks in the perspective of fiqh.